Method for preparing platinum catalyst by using waste lithium battery negative electrode graphite and application of platinum catalyst
By recycling the negative graphite of waste lithium battery, pretreatment, nitrogen doping and platinum-loading treatment, platinum catalyst is prepared, which solves the problems of waste of resources and high production costs, and achieves efficient and economical catalyst production and has good sustainability.
Patent Information
- Application Number
- CN202510220545.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-27
- Publication Date
- 2025-03-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing technology is difficult to effectively recycle and utilize graphite resources in waste lithium batteries, resulting in waste of resources and environmental pollution. At the same time, the production cost of platinum catalysts is relatively high.
The platinum catalyst was prepared by recycling the negative electrode graphite of waste lithium battery, pretreatment, crushing, nitrogen doping and platinum-loading treatment. The method includes adding graphite to the sulfuric acid solution soaking, filtering, drying, then pulverizing and nitrogen doping, and finally loading platinum by electrodeposition technology.
The effective recycling and utilization of graphite in waste lithium batteries is achieved, the production cost of platinum catalysts is reduced, the catalytic efficiency and stability of the catalyst is improved, and the dependence on natural graphite resources is reduced, and it has good sustainability.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalysts, and in particular to a method for preparing a platinum catalyst by using negative electrode graphite of waste lithium batteries and application thereof. Background Art
[0002] Graphite is a key material for the negative electrode of lithium batteries. With the widespread use of electric vehicles and portable electronic devices, the demand for lithium batteries has grown rapidly, while graphite resources are limited. Recycling graphite from waste lithium batteries can effectively alleviate the pressure on natural graphite mining and ensure the sustainable supply of graphite resources. The mining of natural graphite involves complex geological exploration, mining and processing processes. Recycling graphite can reduce dependence on new mineral sources to a certain extent.
[0003] If waste lithium batteries are not recycled properly, the harmful substances in them (such as heavy metals) will cause serious environmental pollution. In the process of recycling graphite, other harmful substances can be processed at the same time to reduce the risk of environmental pollution.
[0004] A platinum catalyst is a catalyst with platinum (Pt) as the main active ingredient. A catalyst is a substance that can change the rate of a chemical reaction while its mass and chemical properties remain basically unchanged before and after the reaction. In many chemical reactions, platinum catalysts can significantly reduce the activation energy of the reaction, making the reaction easier to proceed.
[0005] Platinum catalysts use platinum as the active ingredient only. They are highly active and selective and perform well in some specific reactions. For example, in some hydrogenation reactions, such as hydrogenation of benzene to produce cyclohexane, platinum monometallic catalysts can effectively hydrogenate the unsaturated double bonds in the benzene molecule with high reaction selectivity, mainly producing cyclohexane with little other byproducts.
[0006] The invention applies the recycled graphite to the production of platinum catalyst, which not only reduces the production cost but also avoids the waste of waste lithium batteries.
[0007] Based on this, we proposed a method for preparing platinum catalyst using graphite from the negative electrode of waste lithium batteries. Summary of the invention
[0008] In view of the deficiencies in the prior art, the present invention provides a method and application of preparing a platinum catalyst using negative electrode graphite of waste lithium batteries.
[0009] To achieve the above-mentioned purpose, the present invention provides the following technical solutions: A method for preparing a platinum catalyst using waste lithium battery negative electrode graphite comprises the following steps: (1) Recycling of negative electrode graphite from waste lithium batteries; (2) adding the obtained waste lithium battery negative electrode graphite to a sulfuric acid solution for immersion, stirring for 1-1.5 hours, and then filtering, washing, and drying to obtain pretreated waste lithium battery negative electrode graphite; (3) crushing and grinding the above-mentioned pre-treated waste lithium battery negative electrode graphite to obtain graphite crushed material; (4) The graphite powder obtained above is subjected to nitrogen doping treatment to obtain a nitrogen-doped material; the preparation method of the nitrogen-doped material is as follows: First, cellulose and sodium carbonate are added to a blender in sequence, and stirred and mixed evenly to obtain a primary mixture; The obtained primary mixed material is added into a tubular furnace, and heated to 750-780°C at a heating rate of 5°C / min under the protection of a nitrogen atmosphere, and then kept at this temperature for 1.5 hours, and then cooled to room temperature to obtain a primary calcined material; The obtained primary calcined material is added to a sulfuric acid aqueous solution, stirred and reacted for 1 hour, then filtered, washed to neutrality, and dried to obtain a preliminary material; The obtained preliminary material, graphite crushed material and melamine are sequentially added into a mixer, and stirred and mixed evenly to obtain a secondary mixture; The secondary mixed material is heated to 900-920°C at a heating rate of 10°C / min in a tubular furnace under the protection of a nitrogen atmosphere, and then kept warm for 1.5 hours, and then cooled to room temperature to obtain a nitrogen-doped material; (5) The nitrogen-doped material is subjected to platinum loading treatment to obtain a platinum catalyst; the platinum loading treatment is as follows: The nitrogen-doped material was added to the electrolyte and electrodeposition was performed using cyclic voltammetry in the voltage range of -0.3-0.2 V at a scan rate of 20 mV·s -1 , electroplating for 45 turns, that's it.
[0010] As a further technical solution, in step (2), the waste lithium battery negative electrode graphite is added to the sulfuric acid solution in a mixing ratio of 20-30 g: 300 mL; The mass fraction of the sulfuric acid solution is 40%.
[0011] As a further technical solution, the soaking temperature in step (2) is 70° C., and the washing is performed using deionized water until it becomes neutral; The drying was carried out at 80° C. for 4 hours.
[0012] As a further technical solution, the graphite powder in step (3) is crushed and ground and then passed through a 120-mesh sieve to obtain a graphite powder.
[0013] As a further technical solution, the mass ratio of the cellulose to the sodium carbonate is 1:2; The mixing ratio of the primary calcined material and the sulfuric acid aqueous solution is 10-15g:200mL; The mass fraction of the aqueous sulfuric acid solution is 25%.
[0014] As a further technical solution, the mixing mass ratio of the preliminary material, the graphite crushed material and the melamine is 1:10:5.
[0015] As a further technical solution, the electrolyte includes 0.5 mol / L sulfuric acid, 5.368×10 -3 mol / L chloroplatinic acid, the rest is water; The mixing mass ratio of nitrogen-doped material to electrolyte is 1:10.
[0016] A platinum catalyst obtained by a method of preparing a platinum catalyst using waste lithium battery negative electrode graphite is applied in the field of catalysis.
[0017] Compared with the prior art, the present invention provides a method for preparing a platinum catalyst using graphite from the negative electrode of waste lithium batteries, which has the following beneficial effects: The use of recycled negative electrode graphite from waste lithium batteries to prepare platinum catalysts has a relatively obvious cost advantage. Since the negative electrode graphite of waste lithium batteries is widely available, the number of waste lithium batteries is increasing with the widespread use of electric vehicles and portable electronic devices. Recycling the negative electrode graphite can turn waste into treasure. Compared with directly using new graphite materials to prepare platinum catalysts, the cost will be greatly reduced. This is because the mining and processing of new graphite materials require a lot of capital investment, and recycling graphite reduces these initial costs to a certain extent. Therefore, from an economic point of view, recycling the negative electrode graphite of waste lithium batteries for the preparation of platinum catalysts can effectively reduce the production cost of the catalyst. For large-scale chemical production and other application scenarios, this can save a lot of raw material procurement costs while ensuring catalytic performance.
[0018] The loading of the negative electrode graphite platinum nanoparticles after the treatment of the present invention provides a good carrier, and the platinum nanoparticles can be evenly dispersed in the graphite carrier, which can avoid the agglomeration of the platinum particles. In the catalytic reaction, the agglomerated platinum particles will reduce their effective active sites, while the evenly dispersed platinum nanoparticles can expose the active sites to the maximum extent, thereby improving the catalytic efficiency of the catalyst.
[0019] Since graphite itself is an excellent conductive material, this high conductivity helps the transmission of electrons in the process of preparing platinum catalysts. In some electrocatalytic reactions, electrons can be quickly transferred between platinum catalysts and electrodes, thereby accelerating the reaction. It can be seen that platinum catalysts prepared from recycled graphite also have good application prospects in the field of electrocatalysis.
[0020] The recycling and reuse of graphite from the negative electrodes of waste lithium batteries reduces the over-exploitation of natural graphite resources. From the perspective of sustainable development, this is a way of recycling resources and can alleviate the pressure of graphite resource shortage. DETAILED DESCRIPTION
[0021] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0022] Example 1
[0023] A method for preparing a platinum catalyst using waste lithium battery negative electrode graphite comprises the following steps: (1) Recycling of negative electrode graphite from waste lithium batteries; (2) adding the obtained waste lithium battery negative electrode graphite to a sulfuric acid solution for immersion, stirring for 1 hour, and then filtering, washing, and drying to obtain pretreated waste lithium battery negative electrode graphite; the waste lithium battery negative electrode graphite is added to the sulfuric acid solution in a mixing ratio of 20g:300mL; The mass fraction of the sulfuric acid solution is 40%; the soaking temperature is 70° C., and the washing is performed using deionized water until it is neutral; The drying was carried out at 80° C. for 4 hours.
[0024] (3) The pretreated waste lithium battery negative electrode graphite is crushed and ground to obtain graphite crushed material; after crushing and grinding, the crushed and ground material is passed through a 120-mesh sieve to obtain graphite crushed material.
[0025] (4) The graphite powder obtained above is subjected to nitrogen doping treatment to obtain a nitrogen-doped material; the preparation method of the nitrogen-doped material is as follows: First, cellulose and sodium carbonate are added to a blender in sequence, and stirred and mixed evenly to obtain a primary mixture; The obtained primary mixed material is added into a tubular furnace, and heated to 750°C at a heating rate of 5°C / min under the protection of a nitrogen atmosphere, and then kept at this temperature for 1.5 hours, and then cooled to room temperature to obtain a primary calcined material; The obtained primary calcined material is added to a sulfuric acid aqueous solution, stirred and reacted for 1 hour, then filtered, washed to neutrality, and dried to obtain a preliminary material; The obtained preliminary material, graphite crushed material and melamine are sequentially added into a mixer, and stirred and mixed evenly to obtain a secondary mixture; The secondary mixed material was heated to 900°C at a heating rate of 10°C / min in a tubular furnace under the protection of a nitrogen atmosphere, and then kept warm for 1.5 hours, and then cooled to room temperature to obtain a nitrogen-doped material; the mass ratio of cellulose to sodium carbonate was 1:2; The mixing ratio of the primary calcined material and the sulfuric acid aqueous solution is 10 g: 200 mL; The mass fraction of the sulfuric acid aqueous solution is 25%; the mass ratio of the preliminary material, the graphite crushed material and the melamine is 1:10:5; (5) The nitrogen-doped material is subjected to platinum loading treatment to obtain a platinum catalyst; the platinum loading treatment is as follows: The nitrogen-doped material was added to the electrolyte and electrodeposition was performed using cyclic voltammetry in the voltage range of -0.3-0.2 V at a scan rate of 20 mV·s -1 , electroplating for 45 cycles; the electrolyte includes 0.5 mol / L sulfuric acid, 5.368×10 -3 mol / L chloroplatinic acid, the rest is water; The mixing mass ratio of nitrogen-doped material to electrolyte is 1:10.
[0026] Example 2
[0027] A method for preparing a platinum catalyst using waste lithium battery negative electrode graphite comprises the following steps: (1) Recycling of negative electrode graphite from waste lithium batteries; (2) adding the obtained waste lithium battery negative electrode graphite to a sulfuric acid solution for immersion, stirring for 1.2 hours, and then filtering, washing, and drying to obtain pretreated waste lithium battery negative electrode graphite; the waste lithium battery negative electrode graphite is added to the sulfuric acid solution in a mixing ratio of 23g:300mL; The mass fraction of the sulfuric acid solution is 40%; the soaking temperature is 70° C., and the washing is performed using deionized water until it is neutral; The drying was carried out at 80° C. for 4 hours.
[0028] (3) The pretreated waste lithium battery negative electrode graphite is crushed and ground to obtain graphite crushed material; after crushing and grinding, the crushed and ground material is passed through a 120-mesh sieve to obtain graphite crushed material.
[0029] (4) The graphite powder obtained above is subjected to nitrogen doping treatment to obtain a nitrogen-doped material; the preparation method of the nitrogen-doped material is as follows: First, cellulose and sodium carbonate are added to a blender in sequence, and stirred and mixed evenly to obtain a primary mixture; The obtained primary mixed material is added into a tubular furnace, and heated to 760°C at a heating rate of 5°C / min under the protection of a nitrogen atmosphere, and then kept at this temperature for 1.5 hours, and then cooled to room temperature to obtain a primary calcined material; The obtained primary calcined material is added to a sulfuric acid aqueous solution, stirred and reacted for 1 hour, then filtered, washed to neutrality, and dried to obtain a preliminary material; The obtained preliminary material, graphite crushed material and melamine are sequentially added into a mixer, and stirred and mixed evenly to obtain a secondary mixture; The secondary mixed material was heated to 915°C at a heating rate of 10°C / min in a tubular furnace under the protection of a nitrogen atmosphere, and then kept warm for 1.5 hours, and then cooled to room temperature to obtain a nitrogen-doped material; the mass ratio of cellulose to sodium carbonate was 1:2; The mixing ratio of the primary calcined material and the sulfuric acid aqueous solution is 13 g: 200 mL; The mass fraction of the sulfuric acid aqueous solution is 25%; the mass ratio of the preliminary material, the graphite crushed material and the melamine is 1:10:5; (5) The nitrogen-doped material is subjected to platinum loading treatment to obtain a platinum catalyst; the platinum loading treatment is as follows: The nitrogen-doped material was added to the electrolyte and electrodeposition was performed using cyclic voltammetry in the voltage range of -0.3-0.2 V at a scan rate of 20 mV·s -1 , electroplating for 45 cycles; the electrolyte includes 0.5 mol / L sulfuric acid, 5.368×10 -3 mol / L chloroplatinic acid, the rest is water; The mixing mass ratio of nitrogen-doped material to electrolyte is 1:10.
[0030] Example 3
[0031] A method for preparing a platinum catalyst using waste lithium battery negative electrode graphite comprises the following steps: (1) Recycling of negative electrode graphite from waste lithium batteries; (2) adding the obtained waste lithium battery negative electrode graphite to a sulfuric acid solution for immersion, stirring for 1.5 hours, and then filtering, washing, and drying to obtain pretreated waste lithium battery negative electrode graphite; the waste lithium battery negative electrode graphite is added to the sulfuric acid solution in a mixing ratio of 30 g: 300 mL; The mass fraction of the sulfuric acid solution is 40%; the soaking temperature is 70° C., and the washing is performed using deionized water until it is neutral; The drying was carried out at 80° C. for 4 hours.
[0032] (3) The pretreated waste lithium battery negative electrode graphite is crushed and ground to obtain graphite crushed material; after crushing and grinding, the crushed and ground material is passed through a 120-mesh sieve to obtain graphite crushed material.
[0033] (4) The graphite powder obtained above is subjected to nitrogen doping treatment to obtain a nitrogen-doped material; the preparation method of the nitrogen-doped material is as follows: First, cellulose and sodium carbonate are added to a blender in sequence, and stirred and mixed evenly to obtain a primary mixture; The obtained primary mixed material is added into a tubular furnace, and heated to 780°C at a heating rate of 5°C / min under the protection of a nitrogen atmosphere, and then kept at this temperature for 1.5 hours, and then cooled to room temperature to obtain a primary calcined material; The obtained primary calcined material is added to a sulfuric acid aqueous solution, stirred and reacted for 1 hour, then filtered, washed to neutrality, and dried to obtain a preliminary material; The obtained preliminary material, graphite crushed material and melamine are sequentially added into a mixer, and stirred and mixed evenly to obtain a secondary mixture; The secondary mixed material was heated to 920°C at a heating rate of 10°C / min in a tubular furnace under the protection of a nitrogen atmosphere, and then kept warm for 1.5 hours, and then cooled to room temperature to obtain a nitrogen-doped material; the mixing mass ratio of cellulose to sodium carbonate was 1:2; The mixing ratio of the primary calcined material and the sulfuric acid aqueous solution is 15 g: 200 mL; The mass fraction of the sulfuric acid aqueous solution is 25%; the mass ratio of the preliminary material, the graphite crushed material and the melamine is 1:10:5; (5) The nitrogen-doped material is subjected to platinum loading treatment to obtain a platinum catalyst; the platinum loading treatment is as follows: The nitrogen-doped material was added to the electrolyte and electrodeposition was performed using cyclic voltammetry in the voltage range of -0.3-0.2 V at a scan rate of 20 mV·s -1 , electroplating for 45 cycles; the electrolyte includes 0.5 mol / L sulfuric acid, 5.368×10 -3 mol / L chloroplatinic acid, the rest is water; The mixing mass ratio of nitrogen-doped material to electrolyte is 1:10.
[0034] The following is a comparative example: Comparative Example 1: On the basis of Example 1, the graphite crushed material is not subjected to nitrogen doping treatment, and the rest of the technical scheme is consistent with the technical scheme of Example 1.
[0035] Comparative Example 2: On the basis of Example 1, the nitrogen-doped material is replaced with untreated waste lithium battery negative electrode graphite, and the rest of the technical scheme is consistent with the technical scheme of Example 1.
[0036] test: The pore size of the catalyst was calculated using the Barrett-Joy1er-Hale1da (BJH) method; Table 1 Average pore size nm Example 1 40 Example 2 45 Example 3 42 It can be seen from Table 1 that the catalyst prepared by the present invention has a relatively low pore size.
[0037] The pore volume of the catalyst was calculated using the Barrett-Joy1er-Hale1da (BJH) method; Table 2 <![CDATA[Pore volume cm 3 / g]]> Example 1 0.73 Example 2 0.78 Example 3 0.75 Comparative Example 1 0.35 Comparative Example 2 0.12 It can be seen from Table 2 that the platinum catalyst prepared by the present invention has a higher pore structure and can improve the catalytic effect of the platinum catalyst.
[0038] Catalytic performance test: At room temperature (25°C) and a space velocity of 9000 mL / (gh), the catalysts of the embodiment and the comparative example were used to remove 5 ppm of ethylene, and the ethylene removal rates of each group were compared (5 h); Table 3 Ethylene removal rate% Example 1 100 Example 2 100 Example 3 100 Comparative Example 1 76.3 Comparative Example 2 55.2 It can be seen from Table 3 that the platinum catalyst prepared by the present invention has a higher catalytic efficiency.
[0039] Continue the above test, and after 15 hours of catalytic treatment, continue the test to compare the ethylene removal rate of each group of catalysts: Table 4 Ethylene removal rate% Example 1 63.2 Example 2 64.5 Example 3 63.6 Comparative Example 1 22.7 Comparative Example 2 3.8 It can be seen from Table 4 that the catalyst prepared by the present invention has a relatively long catalytic stability.
[0040] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a platinum catalyst using waste lithium battery negative electrode graphite, characterized in that: The following steps are involved: (1) Recycling of negative electrode graphite from waste lithium batteries; (2) adding the obtained waste lithium battery negative electrode graphite to a sulfuric acid solution for immersion, stirring for 1-1.5 hours, and then filtering, washing, and drying to obtain pretreated waste lithium battery negative electrode graphite; (3) crushing and grinding the above-mentioned pre-treated waste lithium battery negative electrode graphite to obtain graphite crushed material; (4) The graphite powder obtained above is subjected to nitrogen doping treatment to obtain a nitrogen-doped material; the preparation method of the nitrogen-doped material is as follows: First, cellulose and sodium carbonate are added to a blender in sequence, and stirred and mixed evenly to obtain a primary mixture; The obtained primary mixed material is added into a tubular furnace, and heated to 750-780°C at a heating rate of 5°C / min under the protection of a nitrogen atmosphere, and then kept at this temperature for 1.5 hours, and then cooled to room temperature to obtain a primary calcined material; The obtained primary calcined material is added to a sulfuric acid aqueous solution, stirred and reacted for 1 hour, then filtered, washed to neutrality, and dried to obtain a preliminary material; The obtained preliminary material, graphite crushed material and melamine are sequentially added into a mixer, and stirred and mixed evenly to obtain a secondary mixture; The secondary mixed material is heated to 900-920°C at a heating rate of 10°C / min in a tubular furnace under the protection of a nitrogen atmosphere, and then kept warm for 1.5 hours, and then cooled to room temperature to obtain a nitrogen-doped material; (5) The nitrogen-doped material is subjected to platinum loading treatment to obtain a platinum catalyst; the platinum loading treatment is as follows: The nitrogen-doped material was added to the electrolyte and electrodeposition was performed using cyclic voltammetry in the voltage range of -0.3-0.2 V at a scan rate of 20 mV·s -1 , electroplating for 45 turns, that's it.
2. The method for preparing a platinum catalyst using graphite from the negative electrode of waste lithium batteries according to claim 1, characterized in that: In step (2), the negative electrode graphite of the waste lithium battery is added to the sulfuric acid solution in a mixing ratio of 20-30 g: 300 mL; The mass fraction of the sulfuric acid solution is 40%.
3. The method for preparing a platinum catalyst using graphite from the negative electrode of waste lithium batteries according to claim 1, characterized in that: The soaking temperature in step (2) is 70° C., and the washing is performed using deionized water until the water is neutral; The drying was carried out at 80° C. for 4 hours.
4. The method for preparing a platinum catalyst using graphite from the negative electrode of waste lithium batteries according to claim 1, characterized in that: After the grinding in step (3), the graphite powder is passed through a 120-mesh sieve to obtain a graphite powder.
5. The method for preparing a platinum catalyst using negative electrode graphite of waste lithium batteries according to claim 1, characterized in that: The mass ratio of cellulose to sodium carbonate is 1:2; The mixing ratio of the primary calcined material and the sulfuric acid aqueous solution is 10-15g:200mL; The mass fraction of the aqueous sulfuric acid solution is 25%.
6. The method for preparing a platinum catalyst using graphite from the negative electrode of waste lithium batteries according to claim 1, characterized in that: The mixing mass ratio of the preliminary material, the graphite crushed material and the melamine is 1:10:
5.
7. The method for preparing a platinum catalyst using negative electrode graphite of waste lithium batteries according to claim 1, characterized in that: The electrolyte includes 0.5 mol / L sulfuric acid, 5.368×10 -3 mol / L chloroplatinic acid, the rest is water; The mixing mass ratio of nitrogen-doped material to electrolyte is 1:
10.
8. The platinum catalyst obtained by the method for preparing a platinum catalyst using waste lithium battery negative electrode graphite according to any one of claims 1 to 7 is applied in the field of catalysis.
Citation Information
Patent Citations
Nitrogen doping carbonized bacterial cellulose / graphene / platinum composite nanomaterial and preparation method thereof
CN106410223A
Anti-stacking nitrogen doped three-dimensional graphene and preparation method thereof
CN106732732A
Photocatalyst material with high specific surface area and preparation method thereof
CN110102332A
Platinum-carbon catalyst as well as preparation method and application thereof
CN114122430A
Method for preparing platinum catalyst by adopting waste lithium battery negative electrode graphite and application of platinum catalyst
CN118738415A